Völkerwanderung: the renovation of a concept - Rosolen Junior, Geraldo (Romanitas - Revista de Estudos Grecolatinos, 2023)
This article examines the use of the concept of Völkerwanderung, its emergence and popularization, and highlights what we believe to be a historiographical turn based on the contributions of Klaus Rosen and Walter Pohl in the mid-2000s. They interpret these major migration movements of the fiftieth and sixth centuries in their respective temporal frameworks and abandon a perspective on the ethnic cohesion of Germans from the first century to the formation of nation-states. We have also analyzed how the concept of Völkerwanderung was used by neo-Romanists associated with anti-migration groups to support the idea that large migration contingents tend to destroy the countries, cultures, and peoples in which they settle. It is important to note that the term “barbarian” is used only to refer to non-Romans and does not reflect the pejorative aspects associated with the word.